PENGARUH TINGKAT PENDIDIKAN, PENGALAMAN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN BANK JATIM PUSAT - Amelia Firdaus; Johanes Silalahi (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The results of the study showed a significant influence of variables such as: education level, work experience and job satisfaction on employee performance at Bank Jatim Pusat Surabaya. From the R2 test, the influence of education (X1), work experience (X2), and job satisfaction (X3) on employee performance (Y) at Bank Jatim Pusat Surabaya personnel is indicated by the Adjusted R Square value of 0.330 or 33.0%. Whileother factors not included in the study have an influence of 0.67 or 67.0%. The Ftable value of 8.237> Fcount based on the F test of 2.833. with a significance value of 0.000. Education (X1) Work Experience (X2) and Job satisfaction (X3) simultaneously have a significant effect on employee performance (Y) at Bank Jatim PusatSurabaya employees.